Sprachliche Mittel der Aufmerksamkeitslenkung am Beispiel deutscher Horoskoptexte - Poźlewicz, Agnieszka (Studia Germanica Posnaniensia, 2019)
Press horoscopes are short informative and persuasive texts addressed to a seemingly individualreader, who skims through the text in order to match the content and intention of press horoscopesto his or her ownsituation. The article deals with the selected linguistic means used in German presshoroscopes to draw thereader’s attention to certain text elements. The analysed data consists of extractsfrom press horoscopes inGerman weekly magazines for women (Bild der Frau, Freundin). Theaim of the paper is to investigatedifferent linguistic means (e.g. syntactic, lexical and typographicalones) used to draw the reader’s attentionin order to elaborate their preliminary subclassification.